The Effect of Polysulfone-nanosilica Coating on Mechanical Properties of Kenaf Fibre-Reinforced Polymer Composites - Shahrul Azhar, Ilya Izyan; Jumahat, Aidah; Iyazi Shazana Mohamad; Ummu Raihanah Hashim; Ramzi Khiari (International Journal of Integrated Engineering, 2024)
Natural fibre-reinforced polymer composites have gained significant popularity in various engineering applications, replacing traditional synthetic fibre composites. Due to their desirable characteristics, these composites find extensive use across diverse sectors. This study explores Kenaf fibres' potential-based reinforcement material in polymer composites. The Kenaf fibres are laminated with polyvinyl ester resin, forming a plant-based fibre-reinforced polymer (FRP) composite. Additionally, the research investigates the impact of a thermoplastic coating, namely polyethersulfone (PES), on the mechanical performance of the Kenaf fibre-reinforced polymer composites. PES, a versatile thermoplastic material, holds promise for enhancing the composite's properties. The fabrication involves a compression moulding technique, where polyvinyl ester resin acts as the adhesive agent, effectively bonding the PES thin film with the Kenaf fibres. To comprehensively assess the mechanical performance and durability of the thermoplastic coatings, the composites undergo a series of tests: tensile, flexural, interlaminar shear strength (ILSS) and impact tests. Remarkably, the study reveals that the incorporation of polyethersulfone significantly reinforces the strength of the Kenaf fibre-reinforced polymer composites. Both the PES coating and the PES-nanosilica coating demonstrate positive effects on the mechanical properties of the Kenaf FRP composites, leading to notable enhancements in flexural, tensile, impact, and interlaminar shear strength. Introducing nanosilica particles yields further improvements, surpassing the benefits of the PES-based coating alone. The findings from this research emphasise the potential of PES coating and nanosilica in enhancing the mechanical performance of Kenaf fibre-reinforced polymer composites. These results contribute to the domain of sustainable engineering materials, providing valuable insights for developing and optimising natural fibre-reinforced composites in various industrial applications.